Framing the upshot of Hall current on MHD unsteady nanofluid flow from a rotating spherical body in presence of solar radiation. Issue 1 (31st December 2022) - Sarkar, Amit; Kundu, Prabir Kumar
Abstract : A study evaluating the flow characteristic of an unsteady nanofluid near the stagnation point of a time-dependent spinning sphere under the domination of Hall current, solar radiation and a transverse magnetic field is carried out. Nonlinear ruling PDEs subject to their congruous boundary conditions are transfigured into a system of nonlinear ODEs. The impact of affined parameters on temperature, velocity and concentration distributions has been elucidated utilising tables and graphs. Our study imparts that the fluid velocities along x and z directions are increased for Hall parameter while opposite results have appeared for both temperature and concentration profiles. Again heat transfer rate is increased with the support of the Hall parameter but decreased for the magnetic parameter.